Affordability of Housing: Concepts, Measurement and Evidence - Mark Robinson; Grant M. Scobie; Brian Hallinan (New Zealand Government, The Treasury, 2006)
There has recently been widespread public debate and media attention around housing affordability. This paper discusses the concept of affordability as it applies to housing, examines the approaches used to measure affordability, and then documents the aggregate evidence for New Zealand over the last twenty years. We largely use the Household Economic Survey conducted by Statistics New Zealand to obtain our data. We conclude that affordability is difficult to define and that there is no consensus as to the best way to measure it. Using a range of measures, we examine the trends over time. Our data reveals no long-term trend in affordability when considering all measures. Different measures show different movements over time. Affordability has appeared to move in cycles over the last twenty years.
Keywords: R20; 330; housing; affordability; New Zealand